A SAM (Social Accounting Matrix) approach to the policy decision process - Santos, Susana (2012)
Policy analysis and policy making are parts of the policy decision process for which working tools are needed. A Social Accounting Matrix (SAM) consistent with the national accounts is presented at the level of a country, as a possible working tool intended to support that process. Such a framework will therefore consist of a SAM-based approach. On the one hand, it will involve the presentation of a numerical version of a SAM, constructed from national accounts adapted to the System of National Accounts (SNA). This numerical version will be shown as a device that makes it possible to take a snapshot of the reality under study. On the other hand, it will also involve the presentation of two algebraic versions, with which alternative scenarios will be defined for the measurement of policy impacts. One version will consist of accounting multipliers, and the other version will be a so-called master model. In the latter each cell will be defined with a linear equation or system of equations, whose components will be all the known and quantified transactions of the SNA, using the parameters deduced from the numerical SAM that served as the basis for this model. The national accounts will be adopted as the main source of information. The nominal flows that are representative of that part of a society’s activity that is measured by these accounts will be used to measure the network of linkages and interactions involving institutional sectors, production activities and products, as well as the factors that are involved in the production process. An application will be made of a SAM to the Portuguese case, with a comparison being made of the data obtained from the initial numerical SAM and the numerical versions replicated after running the SAM-based models that are representative of those two algebraic versions. Certain comments will be made about those aspects that are either not measured at all or are poorly measured, or else are not identified, and these will be considered as limitations affecting the work undertaken. Some guidelines will be defined for future research, designed to take the study of the SAM to a deeper level and to improve its use in establishing a suitable framework for explaining the reality of countries and supporting the policy decision process.